Homotopy perturbation method for nonlinear damped generalized regularized long-wave - Bulut, Hasan; Baskonus, H. Mehmet (My University, 2010)
In this paper, we present the solution of the Nonlinear Damped Generalized Regularized Long-Wave Equation (DGRLW) by Homotopy Perturbation Method (HPM). We demonstrate our work by testing numerical examples designed to capture the features of the proposed algorithms. Partial differential equations which arise in real-world physical problems are often too complicated to be solved exactly. And even if an exact solution is attainable the required calculations may be too complicated to be practical or it might be diffucult to interpret the outcome.
Keywords: Homotopy perturbation method; The Nonlinear Damped Generalized Regularized Long-Wave Equation